Repensando a formação em psicologia: uma análise da revisão das diretrizes curriculares nacionais - FERREIRA, Ruan Marcus de Jesus Pinheiro (2023)
The National Curriculum Guidelines- NCG for Psychology Undergraduate Programs, currently established by National Council of Education Resolution No. 5/2011, constitute the regulations that deal with principles, fundamentals, conditions of offer and procedures for planning, implementing, and evaluating this major in Brazil. In 2018, based on a demand from the Ministry of Education, the Federal Council of Psychology organized the review process of the national curriculum guidelines, a process that involved the participation of entities in the area, teachers, professionals, and students from all over the country. The main product of this movement was the report titled “Review of the National Curriculum Guidelines for Psychology Undergraduate Programs (2018)”, which was sent to MEC. Based on this process, the National Council of Education, through the Higher Education Council, published two assessment reports, one in 2019 and the other in 2022, each containing a proposal for an NCG Resolution, both of which were not ratified. The general purpose of this dissertation is to analyze the existing differences and continuities between the text of the current NCGs and the proposed review from the 2019 and 2022 reports. As specific objectives, we defined: to historically delineate the profile of the education and training in Psychology in Brazil from the Minimum Curriculum to the implementation of the NCGs; to situate the NCGs within a national education policy; to reflect on the possible impacts that changes in the NCGs have on training and education in Psychology. We have characterized the present study as descriptive and documentary research linked to the field of historiography of psychology with a focus on public domain documents. As results, we highlight the changes brought by the 2019 and 2022 reports in relation to the current NCGs: 1) the inclusion of the Psychology Major values and principles in the sense of understanding the specific aspects that globalization has about the regional diversity of the country, Latin America and the community of Portuguese-speaking countries; the commitment to building a democratic, sovereign and fair society, promoting citizenship, health and human dignity; the respect for personal, social, cultural and ethical diversity; the concern for the image and social recognition, as well as the recognition of the importance of public policies; 2) the competences follow The International Declaration of Core Competences in Professional Psychology of 2016 and are classified into scientific and professional; 3) flexibility of the teaching modality that does not specify that education and training should happen face-to-face; 4) withdrawal from the self-assessment process of undergraduate programs present in the NCG text; 5) withdrawal from the exemplary list of academic activities to be offered by the undergraduate programs. Despite these changes, we conclude that the NCG review process continues the existing NCG model, making some of the program’s devices more flexible in favor of a commodified perspective of higher education. Therefore, we highlight the need for research that evaluates how the implementation of the NCGs in Psychology programs has an impact on the training and education of psychologists, seeking alternative models that overcome training based on competences, and meet the social demands and specificities of Brazilian society.